Pemberdayaan Masyarakat Melalui Pembentukan Kader Piket Kebersihan Kamar Asrama “PISIKA”di Pondok Pesantren Darul Ihsan Samarinda - Nida Amalia; Azizah Dwi Octavia; Ferry Adiaksyah; Indarmawati Indarmawati; Margita Syavira Risky; Muhammad Youri Jorkaef; Yufita Darusman; Yuliani Yuliani (Pusat Penerbitan Ilmiah Universitas Muhammadiyah Kalimantan Timur, 2020)
Community service activities are carried out at the Darul Ihsan Samarinda Islamic Boarding School in Samarinda from November to December 2019 with the target activities of 53 female Dormitory female students. With the theme of Prevention of Skabies and with the title